BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK KADER DALAM PENYULUHAN DI MEJA 4 PADA POSYANDU DI KELURAHAN NGALIYAN, KOTA SEMARANG - Ninda Ayu Pangestuti; Syamsulhuda BM; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Integrated service post (Posyandu) as one means of basic health services in the community to grow and thrive. Posyanduis one form of Community Based Health Effort (UKBM) carried out by, of and with the community, to empower and provide convenience to the public in order to obtain medical care for mothers, infants and toddlers. The purpose of this study to analyze factors related to the practice of cadres in education at 4 tables on Posyandu in Ngaliyan, Semarang.Types of research with cross-sectional study. Respondents of the study amounted to 76 people. Collecting the information through interviews using a questionnaire. The statistical test used to analyze the relationship between variables using Chi-Square. The results showed 65.8% of health cadres including a category that has a good practice, 92.1% of cadres say there are facilities and supporting infrastructure extension, 82.9% Posyandu cadre say no incentive for Posyandu cadres, 85.5% of cadres say there are guidelines Posyandu, 76.3% said that the training good cadres, cadres 67.1% received support from health agencies and 63.2% posyandu cadre who had the support of the community. There is a relationship between education cadre to cadre practices (p = 0.035), facilities and infrastructure to the practice of cadre (p = 0.008), with the practice of Posyandu cadre training (p = 0.029). There is a significant relationship between cadres education, infrastructure and training of cadres posyandu with practices in education at 4 tables on Posyandu.